Effects of Job Satisfaction, Human Resources Practices and the Market Power Work to Desire Move Work Employee - Indra Kertati; Rasty Yulia; Muhsin Efendi; Wahyu Wirasati (Program Pascasarjana STIE Amkop Makassar, 2023)
PT. Budi Dharma is a chemical industry with products that are general chemical with a level that competition pretty high from the inside country as well as abroad. Competition This demand efficiency in order to produce products at competitive prices. Apart from using technology efficient, existing human resources also determine the level efficiency Which will be generated. Study This based on studies case in PT. Budi Dharma to employee with levels manager, Supervisor, Foreman and Staff by using a quantitative approach. The research population is all employees at the Manager, Supervisor, Officer, Staff, and Foreman levels at PT. Budi Dharma with the total sample is 78 respondents selected by using census techniques. Data analyzed by using descriptive analysis and Partial Least Square (PLS) analysis. From the results of research that done on August – September 2022 show that (1) Satisfaction Work influential negative And significantly to the desire to change jobs of employees at PT. Budi Dharma Bandung, (2) Resource practices humans have a negative and significant effect on the desire to change jobs of employees at PT. Budi Dharma Bandung, (3) The labor market has a positive and insignificant effect on the desire to change jobs employee in PT. Budi Dharma Bandung. Keywords: Satisfaction Work, Practice source Power man, Market power Work, Desire move Work